Local Wisdom in The World of Education - Zainuri Syailendra; Sri Setyaningsih; Herfina (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2026)
This study explores the integration of local wisdom into the education. This research aims to examine how local values ​​such as reciprocal cooperation, deliberation, and respect for cultural diversity can be integrated into modern pedagogical practices to create a more inclusive, adaptive, and humanistic learning environment, using a case study and literature review approach or method. In the face of evolving educational paradigms, local wisdom offers a framework for promoting social responsibility, ethical behavior, and a sense of belonging among students. Integrating these traditional values ​​into the curriculum can foster a deeper connection between students and their cultural roots, while developing essential skills needed in today's interconnected world. This approach not only improves students' academic achievement but also strengthens their character, preparing them for leadership roles in local and global communities. Furthermore, the application of local wisdom in education supports the creation of a more inclusive and participatory learning environment. Values ​​such as reciprocal cooperation emphasize collaboration and teamwork, encouraging students to contribute to society and support each other's success.